Residential property price hike and speculation - Haron, Razali; Ibrahim, Khairunisah (Malaysian Institute of Planners, 2019)
This study analyzes the behaviour of property price in Malaysia by examining factors influencing the residential property prices. It aims to determine whether property prices hike in Malaysia can be explained by the fundamental factors or it is due to other unexplained factors, such as speculation. Findings from the study reveal that most of the factors did have significant influence on property price. In addition, the cointegration analysis indicates that the property price and its factors are cointegrated for all property market segments across states. This implies the presence of a long run relationship between the property price and its determining factors, despite slow adjustment of property price towards equilibrium in the long run. This study concludes that the residential property price hike in Malaysia is impacted by fundamental factors and is not speculative in nature.